A geographical analysis of the rst wave of Covid-19 with reference to highland and lowland regions of India - Pandey, Bindhy Wasini; Singh, Yuvraj; Rani, Usha; Kumar, Roosen; Singh, Archana; Pal, Rikta (National Geographical Journal of India, 2021)
The issue of health has become a major concern in recent years as a result of extensive coverage of media reporting outbreaks of diseases and the spread of deadly infectious diseases around the world. There has been a growing concern over the accessibility and affordability of healthcare facilities. The spread of the ongoing pandemic COVID-19 has been felt all over the world. However, the rate of infection varies across certain regions of the world. There exists intra-regional disparity as well. Recent research shows that there are latitudinal and altitudinal variations in the spread of the COVID-19. This paper studies variation of infection COVID-19 across the highlands of the Indian Himalayan Region (IHR) and the lowland areas in India. The paper also examines the role of geographical spaces in the spread of coronavirus in these regions. The study indicates that place-based effects (altitude, temperature, pollution levels, etc.) on health can be seen in a variety of ways; therefore, locational issues are very important for addressing health questions. The paper also analyses the Spatio-temporal pattern of the COVID-19 pandemic in the study area to understand the nature of the disease in different locations.